ENERGY SAVING AS A DIRECTION OF INCREASING THE SECURITY OF CRITICAL SYSTEMS OF RESIDENTIAL BUILDINGS - DZHEDZHULA, VIACHESLAV; YEPIFANOVA, IRYNA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Housing is the place where people spend a significant amount of their lives. Serious recent challenges - epidemics, hostilities, significant increases in energy costs - require increased attention to the critical infrastructure of housing and their level of energy consumption. The ability to work effectively depends on the living conditions of employees. But it is not always possible to restore the work of influential systems in a timely and high-quality manner. There is an urgent problem in the study of the factors influencing the critical infrastructure of residential buildings and the role of energy-saving in improving the security of these systems.The theoretical basis of the study of critical systems safety and energy saving are the works of such scientists as Yermenchuk O. P., Bugaychuk N.V., Telenik S. S., Vlasyuk O. S., Sukhonos M. K., Molodchenko T.G., Prasol V.M., Kylymnyk І. І., Kolyada T.A., Dombrovska A. V., Brovdiy A. M. and others. Despite the well-known volume of publications related to the security of economic systems, it is important to study the factors influencing the critical infrastructure of residential buildings and the role of energy-saving in improving the security of these systems. The purpose of the article is to form proposals for improving the security of critical infrastructure of housing and separate the role of energy-saving in this process.A general indicator of the level of safety of critical infrastructure of residential buildings is proposed, which is presented as a function in general, or specifically as a sum of expert and analytical values of impact factors. It is determined that the main factors influencing the safety of critical infrastructure of the fourth level - residential buildings are the deterioration of engineering equipment, systems, networks, distribution devices, automation, insulation; autonomy of systems; maintainability; accessibility; level of compliance with modern requirements. Prospects for further exploration are the formation of a model for managing the security of critical infrastructure of residential buildings, taking into account the energy component.
Keywords: safety; reliability; heat supply; water supply; energy conservation